Newcastle Disease in Village Chickens in the Southern and Rift Valley Districts in Ethiopia - Zeleke, Aschalew; Sori, Teshale; Gelaye, Esayas; Ayelet, Gelegay (International Journal of Poultry Science, 2005)
A sero-prevalence study of Newcastle disease in village chickens in Ethiopia was conducted on non-vaccinated chickens raised under traditional backyard management system. The study covered dry and wet districts in the Rift Valley and Southern regions, respectively. Higher sero-prevalence rates of Newcastle disease (NCD) virus antibodies were verified in all the dry areas of the Rift Valley and in part of the wet Southern districts. Haemagglutination Inhibition (HAI) Test was used to analyze 283 chicken sera for NCD virus antibodies and the overall sero-positive rate was found to be 19.78%, (n=283). 22.51 % ( n=191) sero positive chicken were found in the dry areas while 14.13 % (n=92) were positive in the wet areas. Comparison was made on the sero prevalence of dry and wet areas as well as between sexes. Chickens from all dry areas showed various titter of NCD antibody but sera collected from the high mountain wet areas were negative. The differences in the sero prevalence, however, were not statistically significant between the sexes and the agro climatic areas. In this study NCD virus circulation was evidenced in village chickens reared in various parts of Ethiopia.